A Novel Technology for Free Flap Monitoring: Pilot Study of a Wireless, Biodegradable Sensor - Oda, Hiroki; Beker, Levent; Kaizawa, Yukitoshi; Franklin, Austin; Min, Jung Gi; Leyden, Jacinta; Wang, Zhen; Chang, James; Bao, Zhenan; Fox, Paige M. (Journal of Reconstructive Microsurgery, 2020)
Background Accurate monitoring of free flap perfusion after complex reconstruction is critical for early recognition of flap compromise. Surgeons use a variety of subjective and objective measures to evaluate flap perfusion postoperatively. However, these measures have some limitations. We have developed a wireless, biodegradable, and flexible sensor that can be applied to real-time postoperative free flap monitoring. Here we assess the biocompatibility and function of our novel sensor.Methods Seven Sprague–Dawley (SD) rats were used for biocompatibility studies. The sensor was implanted around the femoral artery near the inguinal ligament on one leg (implant side) and sham surgery was performed on the contralateral leg (control side). At 6 and 12 weeks, samples were harvested to assess the inflammation within and around the implant and artery. Two animals were used to assess sensor function. Sensor function was evaluated at implantation and 7 days after the implantation. Signal changes after venous occlusion were also assessed in an epigastric artery island flap model.Results In biocompatibility studies, the diameter of the arterial lumen and intima thickness in the implant group were not significantly different than the control group at the 12-week time point. The number of CD-68 positive cells that infiltrated into the soft tissue, surrounding the femoral artery, was also not significantly different between groups at the 12-week time point. For sensor function, accurate signaling could be recorded at implantation and 7 days later. A change in arterial signal was noted immediately after venous occlusion in a flap model.Conclusion The novel wireless, biodegradable sensor presented here is biocompatible and capable of detecting arterial blood flow and venous occlusion with high sensitivity. This promising new technology could combat the complications of wired sensors, while improving the survival rate of flaps with vessel compromise due to its responsive nature.
Keywords: free flap monitoring; venous occlusion; microsurgery sensor; inflammation